PENGARUH KESADARAN DIRI MASYARAKAT TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT DALAM MENCEGAH BAHAYA COVID-19: STUDI DI KELURAHAN BALUWARTI KOTA SURAKARTA [THE EFFECT OF COMMUNITY SELF-AWARENESS TOWARD CLEAN AND HEALTHY LIVING BEHAVIOR IN PREVENTING THE DANGER OF COVID-19: EVIDENCE FROM BALUWARTI VILLAGE SURAKARTA CITY] - Anugerah Mawarti; Aziz Muslim (Journal of Contemporary Islamic Counselling, 2021)
The clean and healthy life behavior program (PHBS) is an embodiment to provide a learning experience or create a conducive condition for individuals, families, groups, and communities to increase knowledge, attitudes, and behavior in order to apply healthy ways of living in order to support, maintain, and improve health. By applying the pattern of clean and healthy living behavior (PHBS) at home is an effort to empower household members to know, want and be able to practice clean and healthy living behaviors and play an active role in the health movement in the community. Community self-awareness is the process of identifying ourselves with our motivations, preferences and personality and then realizing the influence of these factors on our judgments, decisions and interactions with others. In the current era of information technology, there are more and more individuals who are selfish or have a reduced sense of tolerance, be polite and help each other. This research uses a type of quantitative research that performs hypothesis testing. In this study, the researcher used a research design that refers to experimental research, namely the one group pretest-posttest design. The results of this study indicate that there is an influence of community self-awareness on clean and healthy life behavior (PHBS) in preventing the danger of COVID-19 in Baluwarti Village Surakarta City.